Podcasts Boost Listening Skills in Vocational High School Students: Podcasting Improves Listening Skills for Vocational High School Students - Efendi, Adinda Yulia; Astutik , Yuli (Indonesian Journal of Education Methods Development, 2024)
General Background: Listening skills are essential for effective communication and learning, particularly in language acquisition. Specific Background: In vocational high schools, traditional teaching methods may not adequately engage students or enhance their listening abilities. Knowledge Gap: Despite the potential of digital media, there is limited research on the specific benefits of podcasts in improving listening skills among vocational students in Indonesia. Aims: This study investigates the role of podcasts in enhancing listening comprehension among Class X students at SMK Dian Indonesia through a pre-experimental design. Results: Utilizing pre-test and post-test assessments analyzed via a T-test with SPSS, findings indicate a significant improvement in listening skills, with post-test scores averaging 79.75 compared to pre-test scores of 70.60. Novelty: This research contributes to the literature by demonstrating that podcasts can serve as an effective and engaging educational tool for enhancing listening abilities in a vocational context. Implications: The positive outcomes suggest that integrating podcasts into English language instruction can foster a dynamic learning environment, providing students with diverse content and contexts to practice listening. This approach not only addresses existing gaps in language education but also promotes the adoption of innovative teaching methods in vocational schools, thereby enriching the overall educational experience. Highlights: Significant Improvement: The study found a notable increase in students' listening skills, with post-test scores rising from 70.60 to 79.75. Innovative Learning Tool: Podcasts are introduced as a dynamic and engaging medium for enhancing language comprehension in vocational education. Practical Implications: Integrating podcasts into English instruction can diversify content and contexts, enriching the learning experience for students. Keywords: listening skills, podcasts, vocational education, English learning, student engagement